Resolution of Disputes Regarding the Election of Village Head in Villages in Pringgasela District, East Lombok Regency: Penyelesaian Sengketa Pemilihan Kepala Desa di Desa Sekecamatan Pringgasela Kabupaten Lombok Timur - Kafrawi, Rachman Maulana; Sarkawi; M. Saleh; HA Khair; Marsal, Antonino Pedro (Faculty of Law Hang Tuah University, 2025)
The implementation of the Village Head Election is also a manifestation of the community at the village level practicing direct politics. Based on Law Number 6 of 2014 concerning Villages (Village Law), the regulation of village head elections begins with nomination, voting and determination. However, the regulation regarding the resolution of disputes over the results of village head elections is not included in the Village Law. The regulation regarding disputes over the results of village head elections is stated in Article 37 paragraph (6) of the Village Law. In this article, the authority to resolve disputes over the results of village head elections is the authority of the regent/ mayor. Furthermore, regarding the time period for resolving disputes over the results of village head elections for 30 (thirty) days. This research is based on reports of disputes over village head elections. For this reason, it is necessary to resolve disputes over village head elections in accordance with procedures and laws and regulations. This research is anormative research. The results of this study are expected to be the Settlement of Village Head Election Disputes in accordance with applicable Procedures and Laws.